Can Digenic, Tri-Allelic Inheritance of Variants in STAR and CYP11A1 Give Rise to Primary Adrenal Insufficiency? A Case Report - Ali, Naseer; Maharaj, Avinaash Vickram; Buonocore, Federica; Achermann, John C.; Metherell, Louise A. (Frontiers in Endocrinology, 2022)
An eight-year old South Asian boy presenting with progressive hyperpigmentation was found to have primary adrenal insufficiency (PAI) in the form of isolated glucocorticoid deficiency. Follow up of this boy for nine years, until the age of 17 years showed normal pubertal onset and progression. Molecular evaluation, by targeted next generation sequencing of candidate genes linked to PAI revealed changes in two genes that are intricately linked in the early stages of steroid biosynthesis: compound heterozygous variants in STAR, c.465+1G>A and p.(E99K), plus a heterozygous rs6161 change in CYP11A1. No variants in other known causal genes were detected. The proband’s mother was heterozygous for the c.465+1G>A STAR and rs6161 CYP11A1 variants, while the father was homozygous for the p.(E99K) alteration in STAR but wild-type for CYP11A1. Both parents had normal adrenal cortical function as revealed by short Synacthen tests. The STAR variant c.465+1G>A will lead to abnormal splicing of exon 4 in mRNA and the addition of the p.(E99K), predicted damaging by SIFT and CADD, may be sufficient to cause PAI but this is by no means certain given that the unaffected father is homozygous for the latter change. The rs6161 CYP11A1 variant (c.940G>A, p.(E314K)) has recently been demonstrated to cause PAI in conjunction with a severe rare disruptive change on the other allele, however sequencing of the coding region of CYP11A1 revealed no further changes in this subject. We wondered whether the phenotype of isolated glucocorticoid deficiency had arisen in this child due to tri-allelic inheritance of a heterozygous CYP11A1 change along with the two STAR variants each of which contribute a partial loss-of-function burden that, when combined, is sufficient to cause PAI or if the loss-of-function c.465+1G>A combined with the presumed partial loss-of-function p.(E99K) in STAR could be causative.